Role of ARMS2/HTRA1 risk alleles in the pathogenesis of neovascular age-related macular degeneration - Yang Pan; Takeshi Iwata (Taiwan Journal of Ophthalmology)
Age-related macular degeneration (AMD) is one of the leading causes of severe irreversible blindness worldwide in the elderly population. AMD is a multifactorial disease mainly caused by advanced age, environmental factors, and genetic variations. Genome-wide association studies (GWAS) have strongly supported the link between ARMS2/HTRA1 locus on chromosome 10q26 and AMD development, encompassing multiple variants, rs10490924 (c.205G > T, p.A69S in ARMS2), insertion/deletion (del443/ins54 in ARMS2), and rs11200638 (in HTRA1 promoter region). In this comprehensive review, we provide an overview of the role played by ARMS2/HTRA1 risk alleles in neovascular AMD pathogenesis, covering GWAS, in vitro studies, and animal models, shedding light on their underlying molecular genetic mechanisms. Further extensive research is also imperative, including confirmation of these findings, identifying novel treatment targets, and advancing primary and secondary prevention strategies for AMD.